Crosstalk of Humoral and Cell-Cell Contact-Mediated Signals in Postnatal Body Growth - Xuefeng Jing; Masayasu Miyajima; Takahiro Sawada; Qingfa Chen; Keiji Iida; Kenryo Furushima; Daiki Arai; Kazuo Chihara; Kazushige Sakaguchi (Cell Reports, 2012)
The growth hormone (GH)–insulin-like growth factor 1 (IGF1) axis mediates postnatal body growth. The GH receptor has been regarded as the sole receptor that mediates the Janus kinase 2 (JAK2)/signal transducers and activators of the transcription 5B (STAT5B) signal toward IGF1 synthesis. Here, we report a signaling pathway that regulates postnatal body growth through EphA4, a member of the Eph family of receptor tyrosine kinases and a mediator of the cell-cell contact-mediated signaling. EphA4 forms a complex with the GH receptor, JAK2, and STAT5B and enhances Igf1 expression predominantly via the JAK2-dependent pathway, with some direct effect on STAT5B. Mice with a defective Epha4 gene have a gene dose-dependent short stature and low plasma IGF1 levels. Igf1 messenger RNA (mRNA) in the liver and many other tissues was also significantly reduced in Epha4-knockout mice, whereas pituitary Gh mRNA and plasma GH levels were not. These findings suggest that the local cell-cell contact-mediated ephrin/EphA4 signal is as important as the humoral GH signal in IGF1 synthesis and body size determination.